Classroom Management among Pre-service Elementary Teachers in Buguias - Aguindang, Alfred (Journal of Interdisciplinary Perspectives, 2025)
The educators, who are the classroom supervisors, determine a suitable learning environment. Classroom management is essential in creating this kind of learning environment, which becomes a struggle for beginning teachers, including pre-service teachers. This study examines the level and relationship of awareness and knowledge concerning various classroom management approaches. Specifically, it discovered the (1) level of awareness and knowledge of Pre-service elementary teachers regarding classroom management, and the (2) relationship between awareness and knowledge of the different classroom management approaches. Prior research indicates a necessity to examine pre-service teachers' awareness and knowledge of classroom management. A structured questionnaire based on Ornstein's discussion was distributed to all pre-service elementary teachers formally enrolled in the campus's teacher education program. The means were analyzed using a Pearson correlation to comprehend the relationship between the levels of awareness and knowledge. Data analysis indicated elevated levels of awareness and knowledge, along with a positive association between these two variables. This suggests that a pre-service teacher's awareness is likely correlated with their expertise. The findings indicate that pre-service elementary teachers possess awareness and expertise in various classroom management strategies. It is recommended that teacher education programs continue to emphasize both the theoretical and practical applications of diverse classroom management approaches. Further research could explore the long-term impact of this strong foundation on their actual classroom practices and students’ outcomes once they enter the profession. Additional research may be conducted to corroborate the study's findings.